1999
DOI: 10.1161/01.cir.100.11.1242
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of Neurally Mediated Syncope

Abstract: Abstract-A wide variety of pharmacological agents are currently used for prevention of recurrent neurally mediated syncope, especially the vasovagal faint. None, however, have unequivocally proven long-term effectiveness based on adequate randomized clinical trials. At the present time, ␤-adrenergic receptor blockade, along with agents that increase central volume (eg, fludrocortisone, electrolyte-containing beverages), appear to be favored treatment options. The antiarrhythmic agent disopyramide and various s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 64 publications
0
33
0
4
Order By: Relevance
“…4 -6,23 In general, pharmacological treatment is usually considered the first option for the prevention of recurrent vasovagal episodes, even if the evidence in favor of such an approach is scarce. 5,6 Moreover, long-term compliance with drug therapy is far from satisfactory, with side effects or adverse reactions causing frequent withdrawals. 5,6 Conversely, recent studies have suggested that cardiac pacing may significantly relieve symptoms in specific subsets of highly symptomatic vasovagal fainters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 -6,23 In general, pharmacological treatment is usually considered the first option for the prevention of recurrent vasovagal episodes, even if the evidence in favor of such an approach is scarce. 5,6 Moreover, long-term compliance with drug therapy is far from satisfactory, with side effects or adverse reactions causing frequent withdrawals. 5,6 Conversely, recent studies have suggested that cardiac pacing may significantly relieve symptoms in specific subsets of highly symptomatic vasovagal fainters.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Consequently, highly symptomatic subjects with excessive lifestyle difficulties are usually considered for a specific treatment. 4,5 In general, the available therapeutic options for vasovagal syncope can be broadly classified as long-term pharmacological therapy and permanent dual-chamber cardiac pacing. 4 -6 Although medical therapy should be effective in preventing the development of the vasovagal reflex, cardiac pacing is expected to contrast the reflex just after its appearance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…44 Elimination is via the urine. 44 No pharmacokinetic evaluation of midodrine and its metabolite in patients with type 1 HRS has been performed. Previous clinical studies conducted in these patients used different doses of midodrine (Table 4).…”
Section: The Use Of Vasoconstrictors For Type 1 Hrsmentioning
confidence: 99%
“…), which are γ-aminobutyrate A (GABA A ) receptor antagonists 25,26) or WAY-100635 (0.5 mg/kg, i.p. ), which is a 5-HT 1A receptor antagonist, 27) in mice exposed to immobilization stress (Fig. 2).…”
Section: Effect Of Flumazenil Bicuculline and Way-100635 On The Anximentioning
confidence: 98%